The fern family Blechnaceae:old and new genera re-evaluated, using molecular data - André Luís de Gasper (2016)
Blechnaceae is a monophyletic family of worldwide distribution, having Blechnum occidentale L. as type species. The family is characterized by petioles with two or more vascular bundles at the base, commissural vein parallel to the costae, cenosori borne on these commisural veins, indusia opening inwardly, and reddish young fronds. The family was divided, traditionally, into two major groups, the monomorphic and dimorphic species, however, this division has been questioned. The first classification proposed follow this division and two genera was accepted: Blechnum L. and Lomaria Willd., but afterwards others proposes was made. The proposal so far adopted was elaborated in the 90s, where nine genera were recognized in two subfamilies, being Blechnum, Brainea J. Sm., Doodia R. Br., Pteridoblechnum Hennipman, Sadleria Kaulf., Salpichlaena J. Sm., Steenisioblechnum Hennipman and Woodwardia Sm. in Blechnoideae, and, Stenochlaena Ching in Stenochlaenoideae. The highest species richness is in the genus Blechnum that is also sub-cosmopolitan, with two main diversity centers in Neotropics and Oceania. More recently a new genus was recognized, Telmatoblechnum Perrie et al., with the segregation of two species of Blechnum, and Doodia, Steenisioblechnum and Pteridoblechnum were included in Blechnum However, even then Blechnum remained paraphyletic. In order to test the congruence of the genera, we have assembled the broadestsequence dataset thus far (ca. 60%), including three plastid regions (rbcL, rps4-trnS, trnL-trnF intergenic spacer region) and with taxonomic sampling focused on both major diversity centers. Our sampling includes 160 taxa and 183 newly generated sequences. We recognize three subfamilies, all with high support in the three analyzes performed: Maximum Parsimony, Maximum Likelihood and Bayesian Inference. The genera Salpichlaena, Stenochlaena, and Telmatoblechnumare monophyletic, but Blechnum, in its current (historical) circumscription is polyphyletic, because Brainea, Doodia, and Sadleria all nest within it. Based on these results, we propose the recognition of 24 genera, been six new and the other resurrected, and new combinations for allspecies.In addition, descriptions an identification key for all genera was prepared.